Research on security evaluation system of network information system based on rough set theory. Issue 3 (31st August 2021) - Chen, Jia; Miao, Yingkai
In view of the poor stability and long response time of the traditional network information system security evaluation system, a rough set based network information system security evaluation system is proposed. Based on the related principles of system safety engineering, the paper constructed the evaluation model of ANN and AHP by using the network topology structure, extracted the basic indexes of related safety evaluation, and processed the basic index data by using the multi-level gray comprehensive evaluation method. Construct the network information system security evaluation index system, use rough set theory to simplify the knowledge, obtain the initial index set, delete the redundant index, and obtain the optimised evaluation index system. The experimental results show that the designed system is more than 80% stable and the system response time is less than 1.32 ms, which proves that the designed system is more efficient and stable.